Higher neutrophil-lymphocyte ratio is associated with better prognosis of hepatocellular carcinoma - Li, Sheng-chao (Medicine (Baltimore), 2020)
Hepatocellular carcinoma (HCC) is one of the most common malignant tumors worldwide; its morbidity and mortality have both recently increased. Lately, the role played by the neutrophil-lymphocyte ratio (NLR) in the development of HCC has attracted attention. However, the exact relationship is not fully understood. A total of 538 participants diagnosed with HCC were recruited between 2010 and 2018. Their relevant routine blood parameters were measured, including NLR. Pearson Chi-Squared test, Spearman Rho test, and logistic regression analysis were performed to explore any correlations between NLR and HCC. A receiver operating characteristic (ROC) curve analysis was performed to determine the usefulness of NLR for predicting HCC. Univariate and multivariate Cox regression analysis for relevant routine blood parameters and any relationships with overall survival (OS) were performed. The Kaplan–Meier method was used to explore any further relationships with OS. NLR was significantly correlated with HCC tumor size by Pearson Chi-Squared test (P = .008). Furthermore, Spearman correlation coefficient showed that HCC tumor size was significantly correlated with NLR (P = .115, P = .008). NLR could sensitively and specifically predict HCC tumor size (area under the curve [AUC], 0.605; 95% confidence interval [CI], 0.429–0.743; P = .000). Higher NLR in patients with HCC was correlated with better OS (hazard ratio [HR] = 0.584; P = .000). A close correlation existed between increased NLR and HCC; NLR could sensitively and specifically predict HCC. High NLR might be an independent protective factor in the prognosis of patients with HCC.